2013
DOI: 10.1177/0310057x1304100112
|View full text |Cite
|
Sign up to set email alerts
|

Oseltamivir Pharmacokinetics in Critically Ill Adults Receiving Extracorporeal Membrane Oxygenation Support

Abstract: Extracorporeal membrane oxygenation (ECMO) is known to affect pharmacokinetics and hence optimum dosing. The aim of this open label, prospective study was to investigate the pharmacokinetics of oseltamivir (prodrug) and oseltamivir carboxylate (active metabolite) during ECMO. Fourteen adult patients with suspected or confirmed H1N1 influenza were enrolled in the study. Oseltamivir 75 mg was enterally administered twice daily and blood samples for pharmacokinetic assessment were taken on day 1 and 5. A multi-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 16 publications
1
22
0
1
Order By: Relevance
“…In one prospective population study, the PK parameters of oseltamivir carboxylate in 14 adult ECMO patients were compared with values reported in healthy volunteers. This study demonstrated a significant increase in Vss (179 vs 26 L) during ECMO (Table ) . This might reflect the expanded circulating volume .…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…In one prospective population study, the PK parameters of oseltamivir carboxylate in 14 adult ECMO patients were compared with values reported in healthy volunteers. This study demonstrated a significant increase in Vss (179 vs 26 L) during ECMO (Table ) . This might reflect the expanded circulating volume .…”
Section: Resultsmentioning
confidence: 57%
“…However, critical illnesses, such as oedema, capillary leak syndrome, third spacing and large volumes of blood products administered to patients during ECMO, could also cause expansion of the Vd . The mean CL of oseltamivir carboxylate was significantly decreased in ECMO patients because oseltamivir carboxylate is primarily eliminated renally, and ECMO patients have substantially decreased renal function compared to that of healthy volunteers . Furthermore, they often require CVVHDF, which results in drug accumulation .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7981 Fourteen patients received standard oseltamivir dosing of 75 mg twice daily. 58,81 Mean systemic exposures at this dose were well above the MIC for H1N1 and comparable to those seen in non-ECMO patients and healthy volunteers. However, there was significant variability of PK parameters between patients in this study, which the authors attributed to differences in enteral absorption and renal function.…”
Section: Resultsmentioning
confidence: 99%